Bias perilaku investor dalam mengambil keputusan berinvestasi - Hidajat, Amelia; Margaretha, Farah; Purba, Yosephina (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research aims to analyze the existence of investment decision-making processes by investors that are influenced by investment behavior bias variables and investor types as variables that are thought to moderate the relationship between the investment decisionmaking process and investment behavior bias. The investment behavior bias in the studyfocused on effect disposition behavior bias, habitual behavior bias following community, and excessive trustyadirian behavior bias. The data used in this study is primary data sourced from the results of surveys to investors who invested in stocks on the Indonesia Stock Exchange (IDX) for more than one year. Questionnaires were distributed to respondents and obtained as many as 350 answers of qualified respondents. Data analysis used for hypothesis testing is structural equation modeling (SEM) analysis using smart PLS 3 applications. The results showed that excessive risky behavior bias had a positive and significant influence on the investment decision-making process. In addition, investor type variables are proven to also moderate the direction of negative relationships between habitual behavioral bias following the community in investors and the investment decision-making process. The results of this study provide information that investment behavior bias, especially excessive trust and community habits need to be wary of investors because it can affect the investment decision-making process that may be able to make irrational decision actions.